2007
DOI: 10.1097/ico.0b013e31804f5a45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Topical Thymoquinone on Corneal Neovascularization

Abstract: Thymoquinone was shown to have an inhibitory effect, comparable with that of triamcinolone, on corneal neovascularization in this rat model. However, thymoquinone decreased corneal neovascularization in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…By day 7, neovascularizaiton extended to the margins of the corneal burn. Thus, the endpoint of the study was achieved because the neovascularization in control eyes has a tendency to regress gradually after day 7 [15,16] . Table 1 summarizes the length and number of new vessels in both groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By day 7, neovascularizaiton extended to the margins of the corneal burn. Thus, the endpoint of the study was achieved because the neovascularization in control eyes has a tendency to regress gradually after day 7 [15,16] . Table 1 summarizes the length and number of new vessels in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…All these treatment options used in corneal neovascularization are not ideal treatments because of side effects like thermal injury to adjacent areas, ocular hypertension, cataract formation and vessel recanalization [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work with this model has demonstrated that topical antioxidants suppress the growth of blood vessels in rats [13], implicating reactive oxygen species (ROS) in corneal neovascularization. NADPH oxidase is an important source of ROS that mediates redox signalling in the wound-healing response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, starting on day 15 after sensitization, five drops of 0.4% (w/v) thymoquinone were instilled in the nasal cavity three times per day for 7 days. This dose was shown to be as effective as topical steroids in a model of allergic conjunctivitis [13]. The group 4 rabbits received mometasone furoate 2 puffs/day (100 μg) for 7 days after OVA sensitization.…”
Section: Methodsmentioning
confidence: 99%